Refinement of the Diatom Episome Maintenance Sequence and Improvement of Conjugation-Based DNA Delivery Methods - Diner, Rachel E.; Bielinski, Vincent A.; Dupont, Christopher L.; Allen, Andrew E.; Weyman, Philip D. (Frontiers in Bioengineering and Biotechnology, 2016)
Conjugation of episomal plasmids from bacteria to diatoms advances diatom genetic manipulation by simplifying transgene delivery and providing a stable and consistent gene expression platform. To reach its full potential, this nascent technology requires new optimized expression vectors and a deeper understanding of episome maintenance. Here we present the development of an additional diatom vector (pPtPBR1), based on the parent plasmid pBR322, to add a plasmid maintained at medium copy number in E. coli to the diatom genetic toolkit. Using this new vector, we evaluated the contribution of individual yeast DNA elements comprising the 1.4-kb tripartite CEN6-ARSH4-HIS3 sequence that enables episome maintenance in P. tricornutum. While various combinations of these individual elements enable efficient conjugation and high ex-conjugant yield in P. tricornutum, individual elements alone do not. Conjugation of episomes containing CEN6-ARSH4 and a small sequence from the low GC content 3’ end of HIS3 produced the highest number of diatom ex-conjugant colonies, resulting in a smaller and more efficient vector design. Our findings suggest that the CEN6 and ARSH4 sequences function differently in yeast and diatoms, and that low GC content regions of greater than 500 bp are a potential indicator of a functional diatom episome maintenance sequence. Additionally, we have developed improvements to the conjugation protocol including a higher-throughput option utilizing 12-well plates, and plating methods that improve ex-conjugant yield and reduce time and materials required for the conjugation protocol. The data presented offer additional information regarding the mechanism by which the yeast-derived sequence enables diatom episome maintenance, and demonstrate options for flexible vector design.